The Challenging Management of Cancer: An Immunonephrologist's Perspective - Roberta Fenoglio; Dario Roccatello; Emanuele De Simone; Giulio Del Vecchio; Michela Ferro; Giacomo Quattrocchio; Antonella Barreca; Savino Sciascia (Karger Publishers, 2020)
Introduction: Onconephrology is an emerging medical subspecialization that focuses on the numberless interrelations between cancer and kidney diseases. Tumor cells evade immune surveillance through activation of immune checkpoint pathways that suppress antitumor immune responses. By blocking checkpoints, new anticancer agents disrupt immune homeostasis but potentially induce immune-mediated diseases. Nephrologists and nephroimmunologists should be able to treat the nephrotoxic sequelae of cancer therapy and ensure continuation of the life-saving treatment. Methods: Thirty-seven renal biopsies have been carried out over 42 months in oncologic patients, that is, 5.2% of the total native renal biopsies were carried out in the same period. The commonest diagnoses (>6 cases) were interstitial tubular nephritis, membranous glomerulopathy, IgA nephropathy, vasculitis, and focal and segmental glomerulosclerosis. Case Presentation: Three example cases, including focusing on key questions which could involve the nephrologists are reported in detail. They include a cancer-related Goodpasture Syndrome, the peculiar toxic effects of pemetrexed on tubular cells, and the intriguing relationship between bevacizumab and cryoglobulinemic glomerulonephritis. Conclusion: As shown by these 3 example cases, nephrologists need to be open-minded with regard to kidney biopsy in order to get a timely diagnosis. Nephrologists also need to improve their knowledge of cancer biology and therapy in order to prevent kidney problems, manage therapy-related immune-mediated disorders, and improve patient life expectancy.